Géis, nanocompósitos e compósitos de pectina preparados utilizando a técnica adaptada de ice template. - César, Natália Reigota (2020)
Byopolymers, such as pectin, have the ability to form gels which allows their use as jelly thickeners in food industries, for example. Porous pectin gels are generally homogeneous, forming a water-rich mesh. Pores are cavities within a material, which in some cases can weaken it because it is a discontinuity, or its presence can favor its use in different applications. One of the techniques used for the production of porous materials is the ice template, or freeze-casting, which uses freezing to obtain these materials. The purpose of this work was to develop a process similar to the ice template, replacing the cold finger with cooling in a domestic freezer without a frost-free system; since this new methogology presents low cost and easy access. After the development of the technique, it was applied in the preparation of porous materials, the Project was developed using formulations of pectin and calcium below the concentration of gelation in diferente concentrations; as well as, nanocomposites were prepared with formulations of pectin, calcium and celulose nanofibril (CNF) also with concentrations below gelation; and finally, composites were prepared with diferente concentrations of pectin, calcium and fibers (obtained from young leaves of Typha domingensis) also with concentrations below gelation. After the satisfactory development of the adapted ice template system, followed by the preparation of the new materials, the selection of the best materials (gels, nanocomposites and composites) was carried out, these were conditioned to compression tests, in addition to being also morphologically characterized. The pre-selected solutions of gels and nanocomposites were tested on porous structures, thus forming pore structures within the pore, these were morphologically characterized; in order to possible application in cell growth. Among all the formulations prepared, after compression test (mechanical strength) and morphological characterization, the best mechanically obtained materials were the weak composites (improved 17,4 times in breaking strength compared to the weak gel), medium (improved 32,2 times in relation to the médium gel) and strong (improved 14,7 times in relation to the strong gel), the best formulation for the formation of pore structures within the pore was that of the gel called very weak, as this diffused porous material forming the expected structure.